On Improving Administrative and Legal Provision of HR Management in State Forensic Institutions and Professional Training of Forensic Experts of the Ministry of Justice of Ukraine - O. V. Kurdes (Bulletin of Kharkiv National University of Internal Affairs)
The problematic issues of administrative and legal provision HR management of state forensic institutions and professional training of forensic experts of the Ministry of Justice of Ukraine have been studied. Specific propositions for improving the regulatory and legal, organizational and methodological provision of this area of ​​activity have been provided. The author has emphasized the need to reform the HR management system of state forensic institutions and professional training of forensic experts, which is a guarantee of filling these institutions with highly qualified personnel.